Impact of improved technologies on productivity and profitability of rapeseed-mustard production at farm level in West Bengal, India (SAARC Journal of Agriculture, 2017)
Ten year study of front line demonstrations (FLDs) on rapeseed-mustard was conducted to assess the potentiality of improvised production technology. In West Bengal, Rapeseed-mustard is the major oilseed crop contributing 53% of total oilseed production of the state. One of the major constraints is low productivity of this crop due to non adoption of recommended package of practices and situation-specific improved varieties by most of the growers. Data used for this study were pertained to FLDs in rapeseed-mustard conducted under Integrated Scheme on Oilseeds, Pulses, Oil palm and Maize (ISOPOM) during 2005-06 to 2014-15. The study revealed 27% yield advantage by the adoption of improved varieties almost with other practices. The other components viz., adoption of right method and time of sowing, seed treatment, application of sulphur and boron, integrated fertilizer and irrigation management, integrated pest and disease management showed 37, 32, 26, 32, 26 and 28% respectively yield advantage over farmers practice. Popularization of these proven technologies to the rapeseed- mustard growers will help them to get higher economic returns with sustainable production system of the state.SAARC J. Agri., 14(2): 126-136 (2016)